HTTP blocking in CN: bbc.com, facebook.com, instagram.com, medium.com, nytimes.com +8 more (China) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in China. Data sourced from CensoredPlanet.
Censorship Incident ID: CN-2026-0003. Severity: critical. Confidence: 85%